Destiny and power the American odyssey of George Herbert Walker Bush - Meacham, Jon. (New York Random House Adudio, 2015)
He was the last of a kind, and his rise, his fall, and his rebirth in the twilight of his life offers a window on a great deal of American history.' Meacham creates an intimate and detailed life story of a man whom many know only through his politics, or from a distance. From interviews and exclusive access to Bush's presidential diaries, Meacham brings Bush and the great American family he came from, vividly to life, beginning with the family's story working in a tool company in the Midwest in the late 1800's and on through George H.W. Bush's childhood in Connecticut, his heroic service in World War II, his decision to strike out on his own and try to create an oil business in Texas, to his political rise to be congressman, ambassador to the U.N., head of the CIA, vice president, then president, and the only man since John Adams to see his son become president. Written with Meacham's trademark compelling narration and historical depth and contemporary insight, this stunning biography reveals the unusual self-reflections, as well as the distinctive American life of a man from the Greatest Generation who pursued a life of service as a guardian of America in the way of Eisenhower, and was one of the last gentlemen in our political world
Keywords: Bush, George, 1924-